Business models and opportunity creation: How IT entrepreneurs create and develop business models under uncertainty. (28th May 2015) - Ojala, Arto
Abstract: How can entrepreneurs develop business models for markets in which the technology is constantly changing—or create business models for markets that do not exist? These are fundamental questions for information technology (IT) entrepreneurs, and for information systems (IS) scholars who seek to develop a theoretical understanding of business models. The case study presented in this paper addressed these questions, demonstrating how a small software firm developed its business model over a 15‐year period in cloud gaming markets. Based on the empirical findings, a preliminary theoretical model is presented. The aim of the model is to increase scholarly understanding of how business models are created and developed in markets in which the future directions of a technology are uncertain. It demonstrates the ways in which a business model may evolve through reassessment and development phases, which can be seen as transition elements linking old and new business models.